2019
DOI: 10.1039/c8nr05772a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning nanostructured surfaces with hybrid wettability areas to enhance condensation

Abstract: The condensation processes on various nanopillar surfaces, including the nucleation, growth and coalescence of nanodroplets are characterized through molecular dynamics simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…If, however, the aim is the study of time-or temperature-dependent properties, such as lattice vibration modes (Rothchild et al, 2019), rotational and translational diffusion (Skarmoutsos et al, 2019), disorder (Hsieh & Yip, 1987), phase transitions (van de Streek et al, 2019) or crystal melting (Anand & Patey, 2018), the use of molecular dynamics (MD) is indispensable. MD allows the capture of structural and dynamical features of crystals (van de Streek et al, 2019; Larsen et al, 2017; Chan, 2015) and surfaces (Yu et al, 2019;Gao et al, 2019) far from equilibrium, coping with the very large number of collective variables in large ensembles of interacting molecules, which are not amenable to a full quantum chemical treatment. Yet, the ability of simulation to reproduce experimental observables depends on the accuracy of the force field.…”
Section: Introduction and Scopementioning
confidence: 99%
“…If, however, the aim is the study of time-or temperature-dependent properties, such as lattice vibration modes (Rothchild et al, 2019), rotational and translational diffusion (Skarmoutsos et al, 2019), disorder (Hsieh & Yip, 1987), phase transitions (van de Streek et al, 2019) or crystal melting (Anand & Patey, 2018), the use of molecular dynamics (MD) is indispensable. MD allows the capture of structural and dynamical features of crystals (van de Streek et al, 2019; Larsen et al, 2017; Chan, 2015) and surfaces (Yu et al, 2019;Gao et al, 2019) far from equilibrium, coping with the very large number of collective variables in large ensembles of interacting molecules, which are not amenable to a full quantum chemical treatment. Yet, the ability of simulation to reproduce experimental observables depends on the accuracy of the force field.…”
Section: Introduction and Scopementioning
confidence: 99%
“…With the increase in nanopillar cross-sectional areas, high-temperature regions (red color in the figure) are reduced, accompanied by a smaller X* , which proves that nanopillars of larger cross-sectional areas accelerate the fluid condensation. Furthermore, the addition of nanopillars can change wetting states on the surface, which may further accelerate the condensation of Ar atoms. , Similar to fins of heat exchangers, nanopillars with the lower temperature can increase heat transfer areas to boost the condensation of the fluid. In addition, nanopillars can also interrupt and redevelop thermal boundary layers, which improve the heat transfer between walls and the fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Both experimental and theoretical investigations revealed that the topography of the solid substrates shows influence on the wetting state and the contact angle of water droplets [24][25][43][44][45][46] . To w and pillar width w. As w < 71.4 Å (42.9 Å), the liquid CO2 droplet favors the Cassie state, while it adopts the Wenzel state as w ≥ 71.4Å (42.9 Å).…”
Section: Resultsmentioning
confidence: 99%